Consideration Of Military Judge In Imposing Additional Punishment Of Dismissal To The Defendant According To Kuhpm - Viola Fitri, Syaiful Munandar (JURIDISCH DENKEN, 2025)
Military Courts have a very important role in upholding law and discipline within the armed forces. The consideration of military judges in imposing additional punishment in the form of dismissal to the defendant, with a focus on cases of premeditated murder. The purpose of writing this article is to find out the basis of the judge's consideration in imposing a criminal verdict in the case of murder and the reasons causing additional punishment in the form of dismissal from military service. This research uses normative method by taking materials from library research or several journals, books, internet media, and refers to Article 26 of KUHPM, while empirical research uses scientific methods such as observation, interviews, and case studies. The complexity and challenges facev4d by military judges in enforcing law and discipline in the military environment, as well as the importance of maintaining the honor of the TNI through fair decisions and in accordance with applicable legal norms. Thus, dismissal does not only function as a sanction, but also as an effort to maintain integrity and morality within the military institution.